2022
DOI: 10.1021/acs.est.1c07381
|View full text |Cite
|
Sign up to set email alerts
|

Insects as Chemical Sensors: Detection of Chemical Warfare Agent Simulants and Hydrolysis Products in the Blow Fly Using LC-MS/MS

Abstract: In this work, blow flies were investigated as environmental chemical sample collectors following a chemical warfare attack (CWA). Blow flies sample the environment as they search for water and food sources and can be trapped from kilometers away using baited traps. Three species of blow flies were exposed to CWA simulants to determine the persistence and detectability of these compounds under varying environmental conditions. A liquid chromatography mass spectrometry (LC-MS/MS) method was developed to detect C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…This structure is also covered with a large number of cone-shaped spines, which further increase its adhesion to provide greater attachment during the expression of pre-spawning behaviour [ 32 , 35 , 36 ]. Some studies have shown through electrophysiological experiments that there are contact chemical sensilla on the legs of insects, which can not only perceive salt, water, sugar, and alkaloids [ 37 , 38 ] but also perceive the host extract [ 39 ] and act as a spawning stimulator [ 40 ]. Through ultramicrostructural observation, it was found that the sawtooth-shaped rigid discs are tapered to a point, which is very similar to the shape of the spore sensillum (SG) on the ovipositor [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This structure is also covered with a large number of cone-shaped spines, which further increase its adhesion to provide greater attachment during the expression of pre-spawning behaviour [ 32 , 35 , 36 ]. Some studies have shown through electrophysiological experiments that there are contact chemical sensilla on the legs of insects, which can not only perceive salt, water, sugar, and alkaloids [ 37 , 38 ] but also perceive the host extract [ 39 ] and act as a spawning stimulator [ 40 ]. Through ultramicrostructural observation, it was found that the sawtooth-shaped rigid discs are tapered to a point, which is very similar to the shape of the spore sensillum (SG) on the ovipositor [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…What is worse, the dispersion of SM in the environment, where it remains active for hours to weeks depending on the ambient temperature and soil pH, further exacerbates the lethal effect of SM. Existing detection methods are largely limited to colorimetric assay, , mass spectrometry, , surface-enhanced Raman spectroscopy, and ion mobility spectroscopy . The main limitations of these technologies are either cost, reliability, sensitivity, ease of use, or all of the above.…”
mentioning
confidence: 99%